Ecoregional distribution of potentially useful species of araceae and bromeliaceae as non-timber forest products in Bolivia - Acebey, A; Kromer, T; Maass, Brigitte L.; Kessler, M (Springer, 2010)
In Bolivia, the plant families Araceae and Bromeliaceae offer numerous non-timber products, including ornamental plants, medicines, foods, and fibers. The economic potential for the utilization of these resources depends critically on the distribution of potentially useful species in different ecoregions in Bolivia. We conducted both a bibliographical revision of uses and ecological field work at 43 sites in the Bolivian Andes and lowlands to assess the potential for sustainable use as suggested by the Rapid Vulnerability Assessment method. The ecological criteria used for the evaluation were abundance (frequency), life form, geographical distribution, and habitat preference. We found that Bolivia has a striking number of potentially useful species of both families but that their potential use differs among ecoregions. Araceae were most species-rich and frequent in the humid lowland and montane forests. In these ecoregions, this family has a particular local importance mainly as traditional medicines and a great potential as ornamental plants. In contrast, economically useful bromeliads are best represented in seasonally dry forest habitats, especially for the production of fibres. Many species of bromeliads, which also occur in humid montane forests, although rare, are potentially important for commercialisation as ornamental species. This study shows that the uses of Araceae and Bromeliaceae are manifold and could be greatly increased through efficient management, although with different strategies according to the different ecoregions.